Comparative Evaluation of Efficiency, Efficacy, and Patient Perception of Caries Excavation Burs in Pediatric Patients: A Randomized Clinical Trial - Arundhati Goyal; Manvi Srivastava; Ritu Khanduja; Kusum Bharti (Journal of South Asian Association of Pediatric Dentistry)
Aim: This in vivo study was aimed to investigate and compare the cutting efficiency, removal of carious dentin (efficacy), and patient comfort while removing caries between newer caries excavation bur (ceramic bur and smart bur) with conventional bur (diamond point). Material and methods: A total number of 75 carious primary molars were selected in pediatric patients and three different types of burs were used for caries excavation which were evaluated and compared for total time taken (efficiency), remaining infected dentin (efficacy), and patient acceptance clinically. Result: Significant difference (p = 0.000) was obtained in terms of efficiency with least time consumed by ceramic bur and highest by smart bur. For efficacy, a significant difference was obtained (p = 0.002), ceramic bur being the most effective in carious dentin removal. For patient acceptance, a significant difference was obtained (p = 0.000), diamond point and ceramic bur were equally acceptable to the patient and the least accepted was smart bur. Conclusion: Ceramic bur proved to be suitable for minimally invasive caries excavation in primary molars as well as comfortable to the pediatric patients because of high cutting efficiency and lesser time consumption.